Euhemerism and its uses : the mortal gods - Pugh, Syrithe (Abingdon, Oxon; New York, NY : Routledge, 2021)
"Euhemerism and Its Uses is an inter-disciplinary volume, bringing together experts on classical, mediaeval and Renaissance literature, theory of myth and religious studies to give the first focussed and all-round view of the phenomenon across the long history of its evolution. Euhemerism--the claim that the Greek gods were historically mortal men and women--originated in the early third century BCE, in an enigmatic and now fragmentary text by the otherwise unknown author, Euhemeros. This work, the Sacred Inscription, has been read variously as a theory of religion, an atheist's manifesto, as justifying or satirizing ruler-worship, as a fantasy travel-narrative, and as an early 'utopia'. Influencing Hellenistic and Roman literature and religious and political thought, and appropriated by early Christians to debunk polytheism while simultaneously justifying the continued study of classical literature, euhemerism was widespread in the middle ages and Renaissance, and its reverberations continue to be felt in modern myth-theory. Yet, though frequently invoked as a powerful and pervasive tradition across several disciplines, it is still under-examined and poorly understood. Filling an important gap in the history of ideas, this volume will appeal to scholars and students of classical reception, mediaeval and Renaissance literature, historiography, and theories of myth and religion"--
OCLC-licensed vendor bibliographic record.
Keywords: Euhemerism; Mythology; Religion; HISTORY / General